Numerical Approach for Nonlinear Dynamics Simulation of Belt-Pulley XY Positioning Mechanism - Homaeinezhad, M. R.; Ebrahimi, M. M. (Engineering Science & Technology, 2024)
In this article, the kinematics and dynamics of the CoreXY mechanism are explored, taking into account the motion of the collar plate. Within such mechanisms, the role of friction in the system dynamics is emphasized, necessitating its careful consideration during the derivation of equations. Friction, manifesting in both static and kinetic forms, can lead to the creation of dead zone regions in the system’s operations. These zones are thoroughly discussed in this paper, and friction is accurately computed in various modes across the system components. Among the significant factors contributing to the creation of dead zones are the tension forces within the belts, whose effects on the mechanical dynamics are also meticulously examined. The impact of dead zones on the system dynamics is revealed through simulation results of the dynamic equations, shedding light on the various scenarios in which actuator inputs fall within or outside these dead zone regions. By employing the equations derived from this article, a comprehensive insight can be gained into the prevalent practice of modeling friction-exposed systems, along with a thorough understanding of the dynamic behavior of the CoreXY mechanism.